Shear behaviour of ambient cured geopolymer concrete beams reinforced with BFRP bars under static and impact loads - Huang, Z.; Chen, Wensu; Hao, Hong; Chen, Z.; Pham, Thong; Tran, Tung; Elchalakani, M. (ELSEVIER SCI LTD, 2021)
The use of fiber reinforced polymer (FRP) bars in GeoPolymer Concrete (GPC) structures has drawn increasing attention in recent years. The application of GPC with basalt fiber reinforced polymer (BFRP) reinforcements in replacing Ordinary Portland cement Concrete (OPC) and steel reinforcements leads to green and sustainable constructions. Currently, very limited studies have been conducted to investigate the performance of GPC beams reinforced with BFRP bars under static loads, but no study on their performance under impact loads has been reported yet in open literature. In this study, ambient-cured GPC beams reinforced with BFRP bars were designed, cast and tested under static and impact loads. The damage mode and quantitative results such as midspan deflection, reinforcement strain, and impact and reaction forces were recorded and analysed. Test results showed that spiral stirrups led to superior performance of the beams under both static and impact loads as compared to conventional rectangular stirrups. The commonly used concrete material model *Mat_072R3 in LS-DYNA was modified based on test data to model GPC material. With the modified GPC material model, numerical models were developed and calibrated against the impact test results. Parametric studies were carried out to investigate the influences of GPC material strength and longitudinal and stirrup reinforcement ratios on the performance of beams subjected to impact loads. It was also found that using steel bars as the compression reinforcements led to better performance because BFRP bars under shear and compression were vulnerable to splitting damage subjected to impact loads.